FAKTOR-FAKTOR KEPUTUSAN PENDUDUK MASUK DALAM PEMILIHAN LOKASI PERUMAHAN DI KOTA BANDA ACEH - Muhammad Razuli; Sugiarto Sugiarto; Taufiq Saidi (Prodi Magister Teknik Sipil Unsyiah, 2020)
The housing complex in Banda Aceh City has been built up and spread to the suburbs. The condition of one housing with other housing is different. This study aims to identify consumer decision factors in choosing housing location, and identify dominant consumer decision factors in choosing housing locations in Banda Aceh City. Respondents in this study were residents entering the city of Banda Aceh. The number of samples in this study was set at 150 people. The sampling technique used was proportionate stratified random sampling. The factors evaluated are accessibility factors, completeness of infrastructure and facilities, facilities, environmental conditions, prices and services, and buildings. Data processing used validity test, and reliability test, while data analysis used descriptive analysis and principal factor analysis (PCA). The results showed that the dominant consumer decision factor in choosing housing locations is accessibility and service factors with a variance of 24.798%. Indicators of accessibility and service factors are proximity to the workplace, proximity to the main road, proximity to the city center, proximity to trade facilities, proximity to educational facilities, proximity to banking service facilities, proximity to government offices, proximity to recreational/ entertainment places, proximity to sports venues, proximity to terminals, ease of reaching locations without significant obstacles, prices according to facilities and infrastructure offered.